Hormonal preparations on the productivity and morphological parameters of potato wart differentiator varieties indicators in culture in vitro - Safronova, T. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To study the impact of hormonal origin preparations under controlled conditions on the ontogenesis and productivity of potato varieties-differentiators in culture in vitro.Methods. The researches conducted in biotechnological laboratory of agriculturaal crops Ukrainian science-research plant quarantine station Institute of Plant Protection NAAS. The Murasige-Skoog (MS) nutrient medium was used with adding of various concentration of growth regulators: Epin-Maxi (2.4-epibrassinolide, 0.012 g/l) and Poteytin (2.6-dimethylpyridine-1-oxide with succinic acid, 0.15 mg/l) in the presence of adenine (0.5 mg/l) in the medium during the experiment. The study was conducted on potato wart cultivar — differentiators of different ripeness groups: Glazurna — early, Chervona Ruta-medium-ripened. The plants were grown in a cultivation room at a 16-hour photoperiod with a lighting intensity of 2000—2500 Lx, a temperature of 21—25°C and an air humidity of 60—80%. Each cultivar cuttings were carried out in the amount of 25 plants, with three times repetition of the experiment.Results. The morphogenesis were the highest in comparison with control during the input into the nutrient medium MS growth medium Epin-Maxxi (0.025 g/l) or Poteytin (0.3 mg/l). The increased ability to grow and form more internodes was recorded on 10—15% on 21 st day of cultivation. The root forming intensity was determined during the present phytohormones adding. The microtubers average number and average mass increased.Conclusions. The researched preparations usage allowed to increase productivity cultivar-differentiators for wart potato in culture in vitro with minimal costs. Growth stimulators Epin-Maxi and Poteytin increased the morphometric indexes at plants during their input into the medium. They favored the culture growth and development. They favored the root-forming of potato plants and microtubers quantity increase. Adenine, is as a component of nucleic acids and coenzymes. It plays an important role in plant metabolism. It favors the effective energy usage and impacts on photosynthesis intensity. It causes the Adenine impact as cytoconin on potato growth, development and resistance to stress factors (drought, excessive moisture nutrient lack).